1971
DOI: 10.1136/gut.12.11.906
|View full text |Cite
|
Sign up to set email alerts
|

Simple atrophic gastritis and gastric carcinoma

Abstract: SUMMARY Gastric carcinoma was detected nine, 10, 18, and 21 years after the biopsy diagnosis of atrophic gastritis in four patients of a group of 40. The gastritis was presumed to be of the simple type. Tests of vitamin B,2 absorption in three patients gave normal results, no gastric autoantibodies were detected in the two patients tested, in all patients histological examination of the gastrectomy specimens revealed a multifocal gastritis differing from the diffuse gastritis of pernicious anaemia and in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

1974
1974
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(51 citation statements)
references
References 30 publications
0
50
0
1
Order By: Relevance
“…49 Australian researchers followed 40 patients with atrophic gastritis for a mean 15 years and observed that gastric cancer occurred in four (10%) of them. 50 A large Japanese study followed 3914 patients with endoscopical signs of atrophic gastritis for a mean 4.4 years. 51 Scoring atrophy macroscopically during endoscopy is an accepted and reportedly adequate method in Japan.…”
Section: Atrophy Metaplasia and Gastric Cancer: Prospective Studiesmentioning
confidence: 99%
“…49 Australian researchers followed 40 patients with atrophic gastritis for a mean 15 years and observed that gastric cancer occurred in four (10%) of them. 50 A large Japanese study followed 3914 patients with endoscopical signs of atrophic gastritis for a mean 4.4 years. 51 Scoring atrophy macroscopically during endoscopy is an accepted and reportedly adequate method in Japan.…”
Section: Atrophy Metaplasia and Gastric Cancer: Prospective Studiesmentioning
confidence: 99%
“…
(Schindler, 1965; Siurala etal., 1966;Walker et al, 1971). Numerous authors have investigated cell proliferation kinetics in normal and atrophic stomach mucosa.
…”
mentioning
confidence: 99%
“…Atrophic gastritis is a pathological condition that may predispose to the development of gastric cancer (Schindler, 1965;Siurala etal., 1966;Walker et al, 1971). Numerous authors have investigated cell proliferation kinetics in normal and atrophic stomach mucosa.…”
mentioning
confidence: 99%
“…Very recently, a meta-analysis showed that Hp eradication reduced the risk of gastric cancer (32). However, also the other type of gastritis, the so-called autoimmune gastritis affecting only the oxyntic mucosa predisposes to gastric cancer (33). Thus, it seems that the gastritis and not Hp itself is the carcinogenic mechanism.…”
Section: Predisposing Conditions For Gastric Cancermentioning
confidence: 99%
“…However, it seems logical to focus on the gastritis since also the so-called autoimmune gastritis predisposes to gastric cancer (33). Moreover, oxyntic gastric atrophy is a common feature in conditions causing gastric cancer (36), and therefore, we recently proposed that hypergastrinemia could be the factor incriminated in Hp gastric carcinogenesis (89).…”
Section: Gastrin and Gastric Carcinomasmentioning
confidence: 99%